REVIEW OF METHODOLOGIES FOR EXTRACTING PLANT-AVAILABLE AND AMORPHOUS SI FROM SOILS AND AQUATIC SEDIMENTS - Sauer D.; Herrmann L.; Saccone L.; Conley D.J.; Sommer M. (My University, 2006)
There is a variety of methodologies used in the aquatic sciences and soil sciences for extracting different forms of Si from sediments and soils. However, a comparison of the published extraction techniques is lacking. Here we review the methodologies used to extract different Si fractions from soils and sediments. Methods were classified in those to assess plant-available Si and those to extract Si from amorphous silica and allophane. Plant-available Si is supposed to comprise silicic acid in soil solution and adsorbed to soil particles. Extraction techniques for plant-available Si include extractions with water, CaCl2, acetate, acetic acid, phosphate, H2SO 3, H2SO4, and citrate. The extractants show different capabilites to desorb silicic acid, with H2SO3, H2SO4 and citrate having the greater extraction potential. The most common extractants to dissolve amorphous silica from soils and aquatic sediments are NaOH and Na2CO3, but both also dissolve crystalline silicates to varying degrees. In soils moreover Tiron is used to dissolve amorphous silica, while oxalate is used to dissolve allophanes and imogolite-type materials. Most techniques analyzing for biogenic silica in aquatic environments use a correction method to identify mineral derived Si. By contrast, in the soil sciences no correction methods are used although pedologists are well aware of the overestimation of amorphous silica by the NaOH extraction, which is most commonly used to extract silica from soils. It is recommended that soil scientists begin to use the techniques developed in the aquatic sciences, since it seems impossible to extract amorphous Si from soils completely without dissolving some of the crystalline silicates. © Springer 2006.
Keywords: ADSORBED SILICA; ALKALINE EXTRACTION METHODS; AMORPHOUS SILICA; BIOGENIC SILICA; DISSOLVED SILICA; SILICIC ACID